The Relationship Between Medication Compliance And Recurring Pulmonary Tuberculosis Incidents In The Working Area Of The Kamoning Public Health Center - Elok Alfiah Mawardi; Atika Jatimi; Ahmadi; Jumrotul Aqobah (Universitas Negeri Surabaya, 2025)
Tuberculosis is an infectious disease caused by the bacterium Mycobacterium tuberculosis, which is spread through the inhalation of droplets. Transmission occurs through airborne particles called droplet nuclei, measuring 1-5 microns. This disease is highly contagious and carries a risk of developing treatment resistance if medication is not taken regularly. Tuberculosis patients must undergo treatment for 6-9 months to prevent the transmission of the disease to others around them. This study aimed to determine the relationship between medication adherence and relapse in tuberculosis patients. The research design used in this study was an analytical cross-sectional design with a population of 49 respondents. The 44 respondents were sampled using a probability sampling technique, specifically a random sampling technique. This study used a medication adherence questionnaire. The research results were processed through editing, coding, scoring, and tabulation, and then analyzed using SPSS using the chi-square test. The results of the study showed that 40 respondents (90.9%) took medication regularly, so they did not need to repeat the treatment. The results of secondary data related to recurrent pulmonary tuberculosis occurred in 2 respondents, with a presentation of 4.5%. A total of 42 respondents, with a presentation of 95.9% were declared completely cured and did not experience a relapse. The results of the chi-square test p-value 0.006 <@=0.05. It was concluded that there is a relationship between medication adherence and the incidence of pulmonary tuberculosis in the work area of ​​the Kamoning Community Health Center.